2022
DOI: 10.1021/acscentsci.1c01490
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific Protein Ubiquitylation Using an Engineered, Chimeric E1 Activating Enzyme and E2 SUMO Conjugating Enzyme Ubc9

Abstract: Ubiquitylation—the attachment of ubiquitin (Ub) to proteins in eukaryotic cells—involves a vast number of enzymes from three different classes, resulting in heterogeneous attachment sites and ubiquitin chains. Recently, we introduced lysine acylation using conjugating enzymes (LACE) in which ubiquitin or peptide thioester is site-specifically transferred to a short peptide tag by the SUMO E2 conjugating enzyme Ubc9. This process, however, suffers from slow kinetics—due to a rate-limiting thioester loading step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
(80 reference statements)
0
14
0
Order By: Relevance
“…In factin contrast to sortase-generated diUbs Oa AEP1-generated diUbs are cleaved by DUBs to a similar extent as diUbs bearing a wt-linker, confirming their functional and structural resemblance to endogenous Ub/Ubl-conjugates. In this sense, Oa AEP1-mediated ubiquitylation complements the approach recently reported by Bode and co-workers that requires the introduction of up to three point mutations into the POI to make it a substrate for Ubc9-mediated ubiquitylation. , Ultimately, we envision that Oa AEP1-mediated generation of Ub and Ubl conjugates may be combined with sortylation to further extend our recently developed approach Ubl-tools (Ubl-topologies via orthogonal sortylation) as a modular and robust tool for accessing defined Ub/Ubl chains where we can place DUB-resistant and DUB-susceptible linkages at defined positions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In factin contrast to sortase-generated diUbs Oa AEP1-generated diUbs are cleaved by DUBs to a similar extent as diUbs bearing a wt-linker, confirming their functional and structural resemblance to endogenous Ub/Ubl-conjugates. In this sense, Oa AEP1-mediated ubiquitylation complements the approach recently reported by Bode and co-workers that requires the introduction of up to three point mutations into the POI to make it a substrate for Ubc9-mediated ubiquitylation. , Ultimately, we envision that Oa AEP1-mediated generation of Ub and Ubl conjugates may be combined with sortylation to further extend our recently developed approach Ubl-tools (Ubl-topologies via orthogonal sortylation) as a modular and robust tool for accessing defined Ub/Ubl chains where we can place DUB-resistant and DUB-susceptible linkages at defined positions.…”
Section: Discussionmentioning
confidence: 74%
“…In this sense, OaAEP1-mediated ubiquitylation complements the approach recently reported by Bode and co-workers that requires the introduction of up to three point mutations into the POI to make it a substrate for Ubc9-mediated ubiquitylation. 16,46 Ultimately, we envision that OaAEP1mediated generation of Ub and Ubl conjugates may be combined with sortylation to further extend our recently developed approach Ubl-tools (Ubl-topologies via orthogonal sortylation) 29…”
Section: ■ Conclusionmentioning
confidence: 99%
“…2 ). Moreover, a recent study demonstrated that replacing the SCCH domain of UBA1 with the one of UBA2 allows the engineered UBA1 to load ubiquitin onto the E2 of SUMO (UBC9) 23 . Consequently, we assumed that the SCCH domain of UBA6 may hold specificity to USE1 and thus mutating the above-mentioned positive charged residues in UBA6 may affect the binding to USE1.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of reaction setup, the in vitro procedure allowed us to introduce a variety of synthetic and recombinant thioesters under controlled conditions. We have recently reported an engineered E1 enzyme that can activate and load ubiquitin onto Ubc9 in the cytoplasm of E. coli [28] . In the future, this E1 system could conceivably be used with an evolved Ubc9 variant to activate and conjugate desired peptide and protein moieties to cages in cellulo .…”
Section: Figurementioning
confidence: 99%
“…We have recently reported an engineered E1 enzyme that can activate and load ubiquitin onto Ubc9 in the cytoplasm of E. coli . [28] In the future, this E1 system could conceivably be used with an evolved Ubc9 variant to activate and conjugate desired peptide and protein moieties to cages in cellulo .…”
mentioning
confidence: 99%